Researcher‐Supported Professional Learning and Development for Instructors in Adult L2 Programs: Factors Leading to Ongoing Communities of Practice. Issue 3 (4th September 2022) - ABBOTT, MARILYN L.; LEE, KENT K.
Abstract: We describe a longitudinal (5‐year) researcher‐supported initiative designed to strengthen the research–practice link (RPL) and serve as an effective form of situated professional learning and development (PLD) in adult second language programs. We facilitated the formation of and supported 9 professional reading groups of 6–12 instructors ( N = 76). The groups met monthly to discuss peer‐reviewed journal articles to address shared PLD needs. Using retrodictive qualitative modeling, we traced the underlying factors in our RPL initiative that contributed to the rise of ongoing autonomous communities of practice in which instructors continued to engage in monthly cycles of implementing and adapting research knowledge and co‐constructed knowledge and practices gleaned from their reading and group discussions of peer‐reviewed articles. Data included participants' responses to questionnaires, audio recordings of focus group interviews and reading group discussions, and researchers' field notes. The results indicated that different types of communities of practice emerged over time through complex dynamic interactions between multiple factors in the RPL initiative (e.g., researchers, practitioners, and institutional and environmental forces). We discuss how researchers can strengthen the RPL by fostering the development of communities of practice that combine both research and practical knowledge to improve and create new educational practices. Abstract : Graphical abstract: